PROGRAMMING LANGUAGES, THEIR TYPES AND BASICS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
Computer programming is the act of issuing various commands to a computer's microprocessor, telling it when, where, what to change, and what to input or output. In this article, what programming languages are there, the most common programming languages  and their differences.